The use of radon and thoron in balneotherapy - Lazzerini, Fábio Tadeu [UNESP]; Bonotto, Daniel Marcos [UNESP] (My University, 2015)
Radon (222Rn, half-life 3.8 days) is a naturally occurring volatile noble gas formed from the normal radioactive decay series of 238U, according to the following decay sequence: 238U (4.49 Ga, α) → 234Th (24.1 d, β-) → 234Pa (1.18 min, β- ) → 234U (0.248 Ma, α) → 230Th (75.2 ka, α) → 226Ra (1622 a, α) → 222Rn (3.83 d, α) → ... Thoron (220Rn, half-life 56 seconds) is another naturally radioactive volatile noble gas formed in the 232Th decay series according to the sequence: 232Th (14.0 Ga, α) → 228Ra (5.8 a, β-) → 228Ac (6.2 h, β- ) → 228Th (1.9 y, α) → 224Ra (3.7 d, α) → 220Rn (55.6 s, α) → ... Radon and thoron are colorless, odorless, tasteless, chemically inert and radioactive gases produced continuously in rocks and soils through α-decay of 226Ra and 224Ra, respectively, with some atoms escaping to the surrounding fluid phase, such as groundwater and air. They are subjected to recoil at birth, with the emanated fraction relatively to that produced in the solid phase being dependent on factors such as total surface area of solids and concentration/distribution of 238U (226Ra) in the minerals. 222Rn decays to stable lead according to the sequence: 222Rn (3.83 d, α) → 218Po (3.05 min, α) → 214Pb (26.8 min, β-) → 214Bi (19.7 min, β-) → 214Po (0.16 ms, α) → 210Pb (22.3 a, β-) → 210Bi (5 d, β-) → 210Po (138.4 d, α) → 206Pb. 220Rn decays to stable lead according to the sequence: 220Rn (55.6 s, α) → 216Po (0.14 s, α) → 212Pb (10.6 h, β-) → 212Bi (60.6 min, β--64.1% or α-35.9%) → 212Po (0.3 μs, α) or 208Tl (3.0 min, β-) → 208Pb. High 222Rn concentrations occur in groundwaters in many areas where wells are used for domestic water supply, inclusive in small rural water supplies. Some natural processes related to high concentration of radon in groundwater are: low transmissivity zones, uranium content of the source rock, severe chemical weathering, hydrothermal solution, deposition, extensive fracturing and variations in stress in rocks associated with seismicity. Potential health hazards from radon in consuming water have been considered worldwide, especially when groundwaters are utilized for public water supplies, because 222Rn concentrations in surface waters are often less than 3.7 Bq/L, while in groundwater the 222Rn concentrations commonly are 10-100 times higher. Despite the concerns coupled to the health risks due to ingestion of dissolved radon and thoron in drinking water, these radioactive gases have been sometimes used in balneotherapy in view of attributed benefic physiological effects to human health. This chapter reports the results of investigations held elsewhere focusing some of these aspects.